Analysis of Effect of the Magnetization Distribution of Multi-Pole PM on SPMSM Performance Using Equivalent Magnetic Circuit Considering Dead Zone - Jae-Hyun Kim; Kyoung-Soo Cha; Sung-Woo Hwang; Soo-Gyung Lee; Min-Ro Park; Young-Doo Yoon; Myung-Seop Lim (Energies, 2021)
In multi-pole permanent magnets (PMs) such a ring-type PMs, as multi-poles are magnetized in one segment, the ends of each pole are weakly magnetized, which is known as the dead zone. Thus, when analyzing characteristics of the motor with multi-pole PMs, accurate results can be obtained by considering the magnetization distribution. For this reason, this paper proposed an equivalent magnetic circuit (EMC) for external-rotor surface-mounted permanent magnet synchronous motors (SPMSMs) considering the dead zone to analyze the effects of the dead zone on the characteristics of the motor. As the magnetization in the dead zone gradually decreases toward the end of the pole, the magnetization distribution is assumed to have a trapezoidal shape. To describe the magnetization distribution, each pole was divided into several elements, and the equivalent residual magnetic flux density was applied to the elements of the dead zone. Finally, the validity of the proposed EMC was verified by comparing the back electro-motive force and air-gap magnetic flux density obtained by the EMC, finite-element analysis, and test.